Rowing injuries: An updated review - Thornton, J. S.; Vinther, A.; Wilson, F.; Lebrun, C. M.; Wilkinson, M.; Di Ciacca, S. R.; Orlando, L.; Smoljanovic, T. (Sports Medicine, 2017)
Although traditionally seen as a sport for elite schools and colleges, rowing is a founding Olympic event and is increasingly enjoyed by people of all ages and abilities. The sport`s rapidly changing demographics shows significant growth in masters (age 27 years and above) and para-rowing populations. It has further expanded beyond its traditional flatwater format to include the discipline of open-water or coastal rowing, and an increased focus on indoor rowing. Rowing-specific injury research has similarly increased over the last decade since our last review, revealing areas of improved understanding in pre-participation screening, training load, emerging concepts surrounding back and rib injury, and relative energy deficiency in sport. Through a better understanding of the nature of the sport and mechanisms of injury, physicians and other healthcare providers will be better equipped to treat and prevent injuries in rowers.